Achieving Exceptional Tensile Properties and Improved Microstructural Stability in Nanocrystalline Ni Via Amorphous Interfacial Phase by Codepositing Al Nanoparticles. Issue 10 (27th June 2018) - Chhangani, Sumit; Prasad, M.J.N.V.
Abstract : A thin amorphous interfacial phase within microstructure is one of the promising strategies for designing better nanostructured materials. Nickel and Ni–Al nanocomposites fabricated by pulsed electrodeposition are deformed in tension and selected samples are heated to elevated temperatures. Here, the authors report that a well‐dispersed Al nanoparticle, possessing a thin layer of amorphous oxide shell, reinforcement in nanocrystalline Ni matrix enhances tensile strength by ≈60% without losing ductility and also provides better microstructural stability due to existence of local microstructural gradient. Abstract : Microstructurally graded interface includes thick amorphous layer formed upon codepositing Al nanoparticles facilitates significant improvement in the tensile strength of nanocrystalline Ni without much loss of its ductility.